The Utilization of MS-MLPA as the First-Line Test for the Diagnosis of Prader–Willi Syndrome in Thai Patients - Prapasrat, Chanita; Onsod, Preyaporn; Korkiatsakul, Veerawat; Rerkamnuaychoke, Budsaba; Wattanasirichaigoon, Duangrurdee; Chareonsirisuthigul, Takol (Journal of Pediatric Genetics, 2022)
Prader–Willi syndrome (PWS) is a genetic disorder caused by the expression disruption of genes on the paternally inherited allele of chromosome 15q11.2-q13. Apart from clinical diagnostic criteria, PWS is confirmed by genetic testing. Methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) is one of the molecular techniques used to analyze this syndrome. This study aimed to evaluate the concordance of the test results of MS-MLPA with conventional techniques in the diagnosis of PWS in Thai patients. Forty leftover specimens from routine genetic testing (MS-PCR and FISH) were tested to obtain MS-MLPA results. By comparison, perfect concordance was shown between the result of MS-MLPA and those of conventional techniques. In conclusion, MS-MLPA is an accurate and cost-effective assay that can be used to confirm PWS diagnosis with explicit deletion of affected genes.
Keywords: PWS; MS-MLPA; Imprinting disorder